17β-Estradiol Attenuates Intracerebral Hemorrhage-Induced Blood–Brain Barrier Injury and Oxidative Stress Through SRC3-Mediated PI3K/Akt Signaling Pathway in a Mouse Model. (September 2021) - Xiao, Han; Liu, Jianyang; He, Jialin; Lan, Ziwei; Deng, Mingyang; Hu, Zhiping
Estrogen is neuroprotective in brain injury models, and steroid receptor cofactor 3 (SRC3) mediates estrogen signaling. We aimed to investigate whether and how SRC3 is involved in the neuroprotective effects of 17ß-estradiol (E2) in a mouse model of intracerebral hemorrhage (ICH). Ovariectomized female mice were treated with E2 after autologous blood injection-induced ICH. Brain damage was assessed by neurological deficit score, brain water content, and oxidative stress levels. Blood–brain barrier (BBB) integrity was evaluated by Evan's blue extravasation and claudin-5, ZO-1, and occludin levels. SRC3 expression and PI3K/Akt signaling pathway were examined in ICH mice treated with E2. The effect of SRC3 on E2-mediated neuroprotection was determined by examining neurological outcomes in SRC3-deficient mice undergone ICH and E2 treatment. We found that E2 alleviated ICH-induced brain edema and neurological deficits, protected BBB integrity, and suppressed oxidative stress. E2 enhanced SRC3 expression and PI3K-/Akt signaling pathway. SRC3 deficiency abolished the protective effects of E2 on ICH-induced neurological deficits, brain edema, and BBB integrity. Our results suggest that E2 suppresses ICH-induced brain injury and SRC3 plays a critical role in E2-mediated neuroprotection.